Maqashid Sharia and Its Relationship to the Financial Management of Muslim Individuals; Case Study on Indonesian Society - Firda Aulia; Muhammad Syafi’i Antonio; Yaser Taufik Syamlan (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the influence of maqashid sharia objective factors on the income and expenditure of Indonesian people, using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach analysis. The sample of this study consisted of Indonesian people who are Muslim, including those of productive age and have income to analyze and identify the relationship between maqashid sharia factors both in income and in their respective expenses. The results of the study indicate that maintaining religion (Al-din) has a positive and significant impact on both income and expenditure. Meanwhile, maintaining property (Al-mal) has been shown to have a substantial effect on income, but not on expenditure. Maintaining reason (Al-aql) also shows a significant impact on income, but not on expenditure. On the other hand, maintaining descendants (An-nasl) does not show a substantial effect on finances, either in terms of income or expenditure. Maintaining the soul (An-nafs) has a significant effect on expenditure, but not on income. Overall, this study found that income has a significant influence on expenditure, indicating that effective income management is very important in the financial management of Muslim individuals in Indonesia